The influence of music genre on explosive power, repetitions to failure and mood responses during resistance exercise - Moss, S. L.; Enright, K.; Cushman, S. (Psychology of Sport and Exercise, 2018)
Objectives: To investigate the influence of different music genres on the psychological, psychophysical and psychophysiological responses during power-based and strength-based resistance exercises. Design: Repeated-measures counterbalanced design. Method: Sixteen resistance-trained participants completed an explosive power test in the squat and bench exercises at 30% 1RM across no music, electronic dance music, metal and self-selected conditions. Peak and mean values were recorded for power and velocity. A progressive loading protocol assessed the impact of condition on repetitions to failure at 60, 70 and 80% 1RM in the squat and bench exercises. For all tests, recording of heart rate and rating of perceived exertion were completed after every set, blood lactate after protocol completion, and mood states before and after. Results: Using magnitude-based inferences, music either had no effect or a small detrimental effect on power and velocity, depending on the exercise. Repetitions to failure increased by a small to moderate amount for all music conditions compared to no music at low but not high intensities. Self-selected music provided additional small benefits in repetitions than other music conditions. Rating of perceived exertion was similar between self-selected, metal and no music conditions, whereas electronic dance music revealed higher responses. Vigour increased after all music conditions but remained unchanged in no music. Conclusions: Explosive power exercises either remain unchanged or are disadvantaged when completed to music. Various music genres could improve repetition to failure training at low to moderate intensities, although individuals might expect greatest improvements using self-selected music, without concomitant increases in perceived effort.